2005
DOI: 10.1002/glia.20269
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin affects cell motility and actin cytoskeleton distribution of microglia

Abstract: Statin treatment is proposed to be a new potential therapy for multiple sclerosis (MS), an inflammatory demyelinating disease of the central nervous system. The effects of statin treatment on brain cells, however, are hardly understood. We therefore evaluated the effects of simvastatin treatment on the migratory capacity of brain microglial cells, key elements in the pathogenesis of MS. It is shown that exposure of human and murine microglial cells to simvastatin reduced cell surface expression of the chemokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 48 publications
(74 reference statements)
2
32
0
Order By: Relevance
“…Human microglia express mRNA for a broad variety of TLR, and our group and others have reported that activation of microglia via TLR1/2, 2/6, 3, 4, 5, and 8 triggers a rapid inflammatory response (Bsibsi et al, 2002;Jack et al, 2005;Olson and Miller, 2004;Zuiderwijk-Sick et al, 2007). With regard to microglia, statins have been reported to reduce the cell surface expression of immunoregulatory molecules and to inhibit microglia motility and chemotactic behavior by altering actin distribution and reducing chemokine receptor expression at the cell surface (Kuipers et al, 2006;Lindberg et al, 2005;Townsend et al, 2004). Data on the effects of statins on TLR-mediated microglial activation are limited to two studies describing inhibitory effects of lovastatin (LOVA) and/or simvastatin (SIM) on LPS-induced cytokine responses in rat neonatal microglia and in the human microglial cell line CHME-3 (Lindberg et al, 2005;Pahan et al, 1997).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Human microglia express mRNA for a broad variety of TLR, and our group and others have reported that activation of microglia via TLR1/2, 2/6, 3, 4, 5, and 8 triggers a rapid inflammatory response (Bsibsi et al, 2002;Jack et al, 2005;Olson and Miller, 2004;Zuiderwijk-Sick et al, 2007). With regard to microglia, statins have been reported to reduce the cell surface expression of immunoregulatory molecules and to inhibit microglia motility and chemotactic behavior by altering actin distribution and reducing chemokine receptor expression at the cell surface (Kuipers et al, 2006;Lindberg et al, 2005;Townsend et al, 2004). Data on the effects of statins on TLR-mediated microglial activation are limited to two studies describing inhibitory effects of lovastatin (LOVA) and/or simvastatin (SIM) on LPS-induced cytokine responses in rat neonatal microglia and in the human microglial cell line CHME-3 (Lindberg et al, 2005;Pahan et al, 1997).…”
Section: Introductionmentioning
confidence: 94%
“…1) (Goldstein and Brown, 1990). Statin exposure has been reported to affect the expression levels and secretion of a variety of immune mediators thereby modulating both adaptive and innate immune responses amongst which Toll-like receptor (TLR)-induced responses (Grip et al, 2000;Kuipers et al, 2005Kuipers et al, , 2006Kwak et al, 2000;Neuhaus et al, 2002;Youssef et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…An effective T-cell response requires the assistance of costimulatory molecules interacting with their ligands, such as CD80/ CD86, CD28/CTLA4 and CD40/CD154. Statins inhibit constitutive as well as IFN-␥ induced up-regulation of costimulatory molecules, CD80, CD86, CD40 on lymphocytes, macrophages, microglia and endothelial cells (Kuipers et al, 2005b(Kuipers et al, , 2006. Indeed, statins suppress the cytokine-induced maturation of dendritic cells, which consequently fail to express these costimulatory molecules and to induce T-cell response (Yilmaz et al, 2004).…”
Section: Statin Effects Onmentioning
confidence: 99%
“…Indeed, HMGCoA-reductase inhibitors (statins) have been shown to reduce Rac1 association with cell membranes and subsequently reduce Rac1 cellular effects, including cell morphology and phagocytosis [41]. Simvastatin has been shown to inhibit migration of human and murine microglial cells at baseline and in response to chemokine stimulation, with associated distorted actin distribution [42]. This effect is reversed by co-incubation with L-mevalonate, indicating an inhibitory dependence on disruption of the mevalonate pathway and HMG-CoA reductase activity [42].…”
Section: Therapeutic Targeting Of Cancer Cell Migrationmentioning
confidence: 99%
“…Simvastatin has been shown to inhibit migration of human and murine microglial cells at baseline and in response to chemokine stimulation, with associated distorted actin distribution [42]. This effect is reversed by co-incubation with L-mevalonate, indicating an inhibitory dependence on disruption of the mevalonate pathway and HMG-CoA reductase activity [42]. Similarly, treatment of human cultured prostate cancer cells with simvastatin or rosuvastatin reduced colony-forming ability and migration towards the powerful chemoattractant bone marrow stroma, with normal migratory behaviour restored with the addition of mevalonate or GGPP [43].…”
Section: Therapeutic Targeting Of Cancer Cell Migrationmentioning
confidence: 99%